Pemberdayaan Orang Tua untuk Optimalisasi Tummy Time terhadap Head Control Bayi 0–6 Bulan di Posyandu Jatisampurna Bekasi - Nur Fitri Farkhana; Noraeni Arsyad; Dini Nur Alpiah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to analyze the effect of parent empowerment in optimizing tummy time on head control in infants aged 0–6 months at community health posts in Jatisampurna, Bekasi. Early motor development requires adequate sensory–motor stimulation, yet many parents have limited knowledge and practice of prone positioning activities. A quasi-experimental one-group pretest–posttest design was employed involving nine healthy infants selected through purposive sampling. Parents received education and practical training on tummy time and were instructed to implement a home program for two weeks with a minimum duration of 30 minutes per day. Head control was assessed before and after the intervention using the Head Control Scale across prone, supine, pull-to-sit, and supported sitting positions. The results demonstrated improvements in head control scores in all positions, with the most notable gains observed in infants who had lower baseline abilities. The findings indicate that repeated prone stimulation enhances postural control through increased neck and trunk muscle activation and improved sensory–motor integration. Parent empowerment also increased knowledge, adherence to home stimulation, and active participation in child development monitoring. This community-based intervention shows potential as a promotive and preventive strategy to support early motor development through family-centered approaches at primary health services.